The Entrepreneurial Attributes & Effectiveness of Entrepreneurship Program in Malaysia Public University - Usman, Mariana; Hj. Din, Badariah; Zubir Ibrahim, Ahmad (International Journal of Psychosocial Rehabilitation, 2019)
The field of entrepreneurship is a remedy for the unemployment issues nowadays. In the effort to produce more young and skilled entrepreneurs, entrepreneurship education plays an important role through the role of the university in nurturing entrepreneurial attributes. This paper seeks to determine the entrepreneurial attributes that contributed to the increasing number of young entrepreneurs amongst the graduated university students throughout the enforcement of the entrepreneurship education program. This study follows the quantitative approach, and a survey-based instrument is used to analyze the perceptions of Malaysian public university students. The collected data is analyzed using Statistical Package for Social Sciences (SPSS) software to attain descriptive statistics that describe the profile of entrepreneurship student perception. The findings of this study have proven that self-efficacy, need for achievement, and locus control impacted the effectiveness of entrepreneurship programs in public universities. This study is limited to students in the Malaysian public universities. Therefore, further research should be conducted amongst the students of private universities and other higher learning institutions in order to gather complete information on the entrepreneurship attribute that contributed to the increasing interest amongst students to be involved in the entrepreneurship field. The finding is essential to assist policymakers in improving the implementation of entrepreneurship education.